Effectiveness of light-emitting diode exposure on photodynamic therapy against Enterococcus faecalis: in vitro study - Nanik Zubaidah; Agus Subiwahjudi; Dinda Dewi Artini; Karina Erda Saninggar (Dental Journal (Majalah Kedokteran Gigi), 2020)
Background: A successful root canal treatment eliminates pathogenic bacteria from infected root canals. The most common bacteria in root canal infections is Enterococcus faecalis (E. faecalis), due to its resistance to medicament and root canal irrigation. A photodynamic therapy (PDT) is a method of root canal disinfection that uses a combination of photosensitisers and light activation to eliminate bacteria in the root canal. The duration of the PDT irradiation results in the production of singlet oxygen and reactive oxygen species (ROS) to eliminate the E. faecalis bacteria. Purpose: To analyse the differences in the duration exposure of photodynamic therapy against the E. faecalis bacteria. Methods: The E. faecalis bacteria culture was divided into seven eppendorf tubes. Group I was a control group, and group II, III, IV, V, VI and VII were treated using PDT consisting of Toluidine Blue O (TBO) photosensitiser and light source irradiation for ten, 20, 30, 40, 50 and 60 seconds, respectively. After incubation, the number of bacteria was calculated by the Quebec Colony Counter and analysed using the Kruskal–Wallis test and the Mann–Whitney test (p <0.05). Results: There was a significant difference between the number of E. faecalis bacteria colonies in each treatment group (p <0.05). Group VI and VII, which had a longer exposure to PDT, showed a smaller amount of E. faecalis bacteria. Conclusion: The longer exposure of PDT results in a smaller amount of E. faecalis bacteria. The light irradiation of 50 seconds is the most effective to eliminate E. faecalis bacteria.